Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Berbasis Pendekatan Saintifik Pada Mata Pelajaran Humas dan Keprotokolan XI OTKP2 SMKN 1 Jombang - Ikka Mauli Sundari; Jaka Nugraha (Universitas Negeri Surabaya, 2020)
Research on the development of textbooks of correspondence subject in the even semester class XI regarding office management automation program at SMKN 1 Jombang aims to study the process of developing textbooks, discuss the feasibility of books, students for textbooks developed by researchers and being studied by, existing textbooks at SMK 1 Jombang, and which have been developed by researchers. This research is a Research and Development (R&D) study with a development model from Borg and Gall that is approved up to 7 stages: potential and problems, combining data, product design, design validation, design revision, product testing, product revision/final product. The subject of the study is a comparison of 20 students of X class majoring in the office administration education study program at SMKN 1 Jombang. The results show the feasibility of textbooks by material experts obtained a percentage of 94,4% with very strong criteria, by linguists obtained a percentage of 91,4% with very strong criteria, and by graphic experts obtained a percentage of 84.8% with very strong criteria. From the overall results of expert validation obtained a percentage of 90,2% with very strong criteria. While the results of evaluations of students conducted through limited trials obtained an average of 81% with very strong criteria. So it can be concluded that textbooks of correspondence subject on the even semester developed are declared to be very suitable to be used as teaching materials at SMKN 1 Jombang.